Clinician-patient movement synchrony mediates social group effects on interpersonal trust and perceived pain - Goldstein, Pavel (J Pain, 2020)
Pain is an unfortunate consequence of many medical procedures, which in some patients becomes chronic and debilitating. Among the factors affecting medical pain, clinician-patient (C-P) similarity and nonverbal communication are particularly important for pain diagnosis and treatment. Participants (N=66) were randomly assigned to the clinician and patient roles and were grouped into C-P dyads. Clinicians administered painful stimuli to patients as an analogue of a painful medical procedure. We manipulated the perceived C-P similarity of each dyad using groups ostensibly based on shared beliefs and values, and each patient was tested twice: Once with a same group clinician (concordant, CC) and once with a clinician from the other group (discordant, DC). Movement synchrony was calculated as a marker of nonverbal communication. We tested whether movement synchrony mediated the effects of group concordance on patients’ pain and trust in the clinician. Movement synchrony was higher in CC than DC dyads. Higher movement synchrony predicted reduced pain and increased trust in the clinician. Movement synchrony also formally mediated the group concordance effects on pain and trust. These findings increase our understanding of the role of nonverbal C-P communication on pain and related outcomes and suggest that interpersonal synchrony may be associated with better patient outcomes, independent of the specific treatment provided.